Distribution of Heavy Metals in Sediments in the Nambo Coastal Waters of Southeast Sulawesi Province - Karmila, Karmila; Irawati, Irawati; Haraty, Syamsul Razak (Jurnal Perikanan dan Kelautan, 2024)
A study was conducted on the distribution of heavy metals in sediments in Nambo Beach, Southeast Sulawesi Province, on July 24, 2022. This study aims to determine the content of heavy metals such as Cu, Pb, and Cd in sediments, determine the size of sediment grains, and assess the level of pollution in sediments on Nambo Beach. Determination of station points using a purposive sampling method with 7 station points. The technique used for heavy metal analysis in sediments is the atomic absorption spectrophotometry (AAS) method. The size of sediment grains is determined using a rock comparator, while to determine the level of pollution, the Geoaccumulation Index (I_Geo), Contamination Factor (CF), and Pollution Load Index (PLI) methods are used. The results of the study obtained showed that the highest content of heavy metals was Cu at all stations with values ranging from 0,011-0,0224 mg/L with an average value of 0,014 mg/L and the highest value was at station 1, Pb Metals, with values ranging from 0,001-0,0106 mg/L with an average value of 0,0033 mg/L and Cd with a relay range of 0,001-0,0025 mg/L and an average value of 0,0017 mg/L. The sedimentary grain sizes scattered on Nambo Beach include silt, clay, fine sand, and very fine sand. For testing the level of heavy metal pollution of Cu, Pb, and Cd in sediments, the results of calculations with the category of unpolluted to lightly polluted for all stations were obtained.